1997
DOI: 10.1176/ajp.154.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in bulimia nervosa

Abstract: A lthough binge eating and purging were observed in women with anorexia nervosa, bulimia nervosa is a relatively recent addition to the medical literature, having been first described in 1979 (1). Consistent with the negative impact that binge eating and purging were observed to have on anorectic patients' outcome (2), bulimia nervosa was termed "an ominous variant of anorexia nervosa." This dire description was tempered with the recognition that "only a brief comment on the prognosis of bulimia nervosa is app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Considering that longitudinal studies on this field adopted either binge eating reduction or diagnostic change as outcome measures [4,28,29,30,31,44], we used two different models to analyze data, according to dimensional (binge eating reduction) and categorical approaches (recovery). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that longitudinal studies on this field adopted either binge eating reduction or diagnostic change as outcome measures [4,28,29,30,31,44], we used two different models to analyze data, according to dimensional (binge eating reduction) and categorical approaches (recovery). …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, different longitudinal studies suggest that the considered clinical variables have a different effect on treatment outcome for the two syndromes: a low remission rate of binge eating episodes has been associated with the severity of body dissatisfaction [28], depression [4], and impulsivity for BN [29,30], and with binge eating [31] and emotional eating at baseline [32] for BED. According to the above-considered studies and theories, eating core psychopathology, impulsivity and mood modulatory mechanisms would show a different pattern of association between BN and BED patients, and could act as different moderators of treatment effects in the two syndromes [33].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of impulsivity are associated with poorer outcomes from BN, 9 and case study intervention work found that reduced impulsivity preceded decreased binge eating, 10 suggesting a link between impulsivity and recovery. Some evidence associates the novelty seeking aspect of impulsivity with recovery from AN; due to the rigidity involved in restriction in AN, decreased inhibition may aid in recovery.…”
mentioning
confidence: 99%
“…This model included daily number of binges as the dependent variable and the following independent variables: (1) number of binges the previous day, (2) use of SB (“SB day” vs. “no-SB day” during the pre-SB period vs. “no-SB day” in the post-SB period), (3) interaction between (1) and (2), (4) age at first diagnosis [26,43], (5) time elapsed between first diagnosis and SB presentation [43], (6) diagnosis (AN versus BN and BED together) [44], (7) co-morbidities associated with impulsivity or mood [23] (presence/absence of substance–related, major depressive, bipolar or borderline personality disorder), and (8) educational level [24]. Participants were set as a random factor over the intercept.…”
Section: Methodsmentioning
confidence: 99%